Schistosomicidal Activity of Dihydrobenzofuran Neolignans. Issue 7 (20th June 2018) - Dias, Herbert J.; Patrocínio, Andressa B.; Pagotti, Mariana C.; Fukui, Murilo J.; Rodrigues, Vanderlei; Magalhães, Lizandra G.; Crotti, Antônio E. M.
Abstract : We have evaluated the antischistosomal activity of synthetic dihydrobenzofuran neolignans (DBNs) derived from (±)‐ trans ‐dehydrodicoumaric acid dimethyl ester (1 ) and (±)‐ trans ‐dehydrodiferulic acid dimethyl ester (2 ) against adult Schistosoma mansoni worms in vitro . Compound4 ((±)‐ trans ‐4‐ O ‐acetyldehydrodiferulic acid dimethyl ester) displayed the most promising activity; at 200 μm, it kills 100 ± 0% of worms after 24 h, which resembles the result achieved with praziquantel (positive control) at 1.56 μm . The hydrogenation of the double bond between C7′ and C8′, the introduction of an additional methyl group at C3′, and a double bond between C7 and C8 decreased the schistosomicidal activity of DBNs. On the other hand, the presence of the acetoxy group at C4 played an interesting role in this activity. These results demonstrated the interesting schistosomicidal potential of DBNs, which could be further exploited. Abstract :